The Effectiveness of Android-Based Learning Media with Appy Pie toward Indonesian Economics Subject - ., Ekawarna; Nasori, Ahmad; Riyadi, Riyo (International Journal of Engineering and Technology, 2018)
This study aims to compare the effectiveness of android-based learning media in improving student learning outcomes in Indonesian economics subject.This quasi experiment research was used the Non-Equivalent Design Group design. The subjects of this research were the second semester of Economics student with Indonesian economics subject. From those subjects, student of class A were selected as experimental group and student of class B as a control group. Data analysis was performed by One-Way Analysis of Variance.The result of the research proved that the learning of Indonesian Economics subject using android-based learning media compared to powerpoint-based learning media, which is shown by the average gain score of students with android-based learning media is higher than powerpoint-based learning media.Â Â